2018
DOI: 10.1186/s13104-018-3331-8
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental assessment of HIV-exposed uninfected and early-treated HIV-infected children: study protocol

Abstract: ObjectiveSub-Saharan Africa has the highest prevalence of children at risk of not achieving their developmental potential, attributable largely to the human immunodeficiency virus (HIV) pandemic coupled with negative environmental factors. Childhood developmental stimulation programmes can mitigate adverse outcomes.MethodsNeonates testing HIV positive at birth will be initiated on antiretroviral treatment (ART) and receive an age-appropriate stimulation program, updated at 3 monthly intervals through the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The effects of HIV infection on development can be overcome with treatment. Three studies investigated the outcomes of HIV care and demonstrated that infected infants and children who received HIV care achieved similar cognitive and motor scores to uninfected children at 6, 12 and 24 months ( 56‐58 ) .…”
Section: Resultsmentioning
confidence: 99%
“…The effects of HIV infection on development can be overcome with treatment. Three studies investigated the outcomes of HIV care and demonstrated that infected infants and children who received HIV care achieved similar cognitive and motor scores to uninfected children at 6, 12 and 24 months ( 56‐58 ) .…”
Section: Resultsmentioning
confidence: 99%
“…After birth, infants enrolled into the IG of the neurodevelopmental study received a standardized set of age‐appropriate developmentally stimulating toys and books, as previously described (Strehlau, van Aswegen, & Potterton, 2018). Starting at birth, every 3 months, the caregiver was provided with an age‐specific information card along with pre‐specified toys and items to help stimulate infant development.…”
Section: Methodsmentioning
confidence: 99%
“…Study participation was voluntary, and non‐participation in the neurodevelopmental trial did not preclude participation in the main trial. The study was approved by the Human Research Ethics Committee of the University of the Witwatersrand (M170653), registered with the Pan African Clinical Trial Registry (PACTR201801002967587), and study protocol published (Strehlau, van Aswegen, & Potterton, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation